The Patellar Arterial Supply via the Infrapatellar Fat Pad (of Hoffa): A Combined Anatomical and Angiographical Analysis. (6th June 2012) - Nemschak, Gregor; Pretterklieber, Michael L.
Abstract : Even though the vascular supply of the human patella has been object of numerous studies until now, none of them has described in detail the rich arterial supply provided via the infrapatellar fat pad (of Hoffa). Therefore, we aimed to complete the knowledge about this interesting and clinically relevant topic. Five human patellae taken from voluntary body donators were studied at the Department of Applied Anatomy of the Medical University of Vienna. One was dissected under the operation microscope, a second was made translucent by Sihlers-solution, and three underwent angiography using a 3D X-ray unit. The results revealed that the patella to a considerable amount is supplied by arteries coursing through the surrounding parts of the infrapatellar fat pad. The latter were found to branch off from the medial and lateral superior and inferior genicular arteries. Within the infrapatellar fat pad, these arteries formed a dense network of anastomoses which are all contributing to the viability of the patellar bone. Due to the rich arterial supply reaching the patella via the infrapatellar fat pad, it seems advisable to preserve the fat pad during surgery of the knee in order to reduce the risk of vascular impairment of the patella.